Self-Esteem and Social Interests of Teachers in the Frame of Individual Psychology - Kepalaitė, Albina (Acta Paedagogica Vilnensia, 2004)
The article discloses the features of teachers in the frame of individual psychology. The sample analysed included subjects (n=106) from different schools of Lithuania. Each subject responded to two instruments: social interest and self-esteem scale. Covariates used were gender, age and teaching experience. Data were analysed via factorial analysis of variance and multiple comparisons by "Paula" software. According to the investigation results, most teachers demonstrate very high, high and average social interest and inferiority feeling level, but this level wasn’t significantly related with age, teaching experience and gender. Inferiority feeling and social interest were not significantly related either. The above results may be explained by the small sample extension. The qualitative data analysis revealed, that compensation of inferiority feeling directed to the social useful side is characteristic for 46 proc. of teachers. The factorial data analysis revealed two groups of indicators, on the basis of which supposition can be made, that differences between ideal and real self-esteem might activate for striving superiority and social interest might direct this striving to the useful side of life.